ANALISIS POTENSI PAJAK BUMI DAN BANGUNAN DI KOTA BEKASI PADA MASA PANDEMI TAHUN 2020 – 2022 - Syafitri, Siti Ishmah; Irawati, Irawati (Jurnal Ilmu Administrasi Publik, 2025)
Land and Building Tax is the highest revenue- generating tax among others in Bekasi City during this pandemic period, as it is controlled and utilized by taxpayers in Bekasi City. Meanwhile, during the pandemic, there was a pensioner tax relief for Civil Servant Retirees and a tax reduction of 20% 50% for taxpayers, as per the extent of the relief. Therefore, during the pandemic, the target set by the Local Revenue Agency was only achieved up to 90%. The purpose of this research is to understand the potential of Land and Building Tax in Bekasi City during the pandemic period from 2020 to 2022, and to identify the efforts made to overcome obstacles in the process of collecting Land and Building Tax, as well as the supporting factors for the collection of Land and Building Tax in Bekasi City. This interview was conducted with 4 informants, namely the BAPENDA Regulator, an Academic, and Taxpayers. The data analysis method used in this research is descriptive, where data was collected through interviews, observations, and documentation methods. The results of this research outline the potential of Land and Building Tax in Bekasi City during the pandemic period from 2020 to 2022.